Longitudinal associations between self-regulation and physical activity behavior following metabolic bariatric surgery; an exploratory study - Sundgot-Borgen, Christine; Baardstu, S.; Bond, D. S.; Sniehotta, Falko F.; Bergh, I.; Mala, T.; Rø, Ø; Kvalem, I. L. (International journal of behavioral nutrition and physical activity, 2025)
Low adherence to moderate-to-vigorous physical activity (MVPA) recommendations among patients undergoing metabolic bariatric surgery (MBS) is common. However, understanding of psychosocial factors that contribute to low adherence levels is limited. Self-regulation plays a key role in MVPA adherence. Still, the longitudinal and bidirectional associations between self-regulation and MVPA in the MBS patient population remains unexplored. This study aimed to investigate how self-regulatory processes of action- and coping planning, and action control, developed over a 1-5-year post-surgery period, and explore longitudinally the direct, indirect, and bidirectional associations between this development in self-regulation and MVPA assessed at 1- and 5-years after surgery. Participants from the Oslo Bariatric Surgery Study (OBSS) completed MVPA-specific self-regulation questionnaires at 1-, 3-, and 5-years post-surgery and wore ActiGraph monitors for seven days at 1- and 5-years to assess daily MVPA. Second-order latent growth curve modeling examined changes in the three self-regulation constructs, followed by path analysis to explore direct, indirect, and bidirectional associations between baseline levels and changes in self-regulation, and MVPA at 1- and 5-years post-surgery. A total of 205 (82.8%), 195 (64.6%), and 79 (26.2%) male and females (77%) participated at 1-, 3-, and 5-years after surgery, respectively. Action- and coping- planning decreased with.52 and.30 sd, respectively, over 1-5 years post-surgery. This indicates a moderate effect size. Action control remained relatively stable. Indirect and bidirectional path analyses showed that only higher levels of action control at 1-year were indirectly associated with higher MVPA at 5-years through their impact on MVPA at 1-year, whereas there were no indications of bidirectional associations from MVPA levels at 1-year to changes in any of the self-regulation constructs over time. After MBS, patients exhibited low self-regulation 1-year post-surgery, and many participants faced growing difficulties in self-regulating over time. Self-regulation at 1-year was positively linked to MVPA, with action control only, being associated with MVPA at 5-years. However, no bidirectional associations from MVPA to self-regulation were found. These findings suggest further research is needed to test interventions targeting action control to improve MVPA adherence and optimize surgical outcomes and overall health after MBS.